Tracing Sources and Stage‐Specific Impacts of Heavy Metal Contamination in Farmed Tilapia (Oreochromis niloticus): Implications for Human Health Risk - Md. Hamidur Rahman; Dalal Sulaiman Alshaya; Haitham Ramadan; KOTB A. Attia; Nadira Sultana; Md. Fazle Rohani; Anugrah Ricky Wijaya; Md. Sazzad Hossain (Veterinary Medicine and Science)
Abstract Objective The levels of five heavy metals—zinc (Zn), lead (Pb), chromium (Cr), cadmium (Cd) and arsenic (As)—in soil, water, feed and fish were investigated in this study at different culture phases (early, nursery, grower and harvest) of Oreochromis niloticus (tilapia). Unlike previous studies that focused on one or two sources, this research provides a comprehensive assessment across all major inputs during the entire production cycle, offering new insight into potential contamination pathways. Results Heavy metal accumulation varied across sources and stages. Cr and As in sediment, and Cr in feed at the early stage, exceeded the permissible boundaries set by the Food and Agriculture Organization (FAO) and the World Health Organization (WHO). As the culture progressed, sediment showed increasing levels of Pb, Cr and As, all surpassing safe thresholds during the nursery to harvest phases. Feed also retained elevated Cr concentrations throughout. In contrast, water samples showed minimal contamination, and heavy metal levels in fish stayed within acceptable bounds for human consumption, although Zn and Cr gradually increased toward harvest. These findings suggest that sediment and feed are the primary sources of heavy metal accumulation, with water contributing minimally. Conclusion The results indicate that tilapia raised in contaminated environments may not pose an immediate risk to consumers, but long‐term exposure through sediment and feed can lead to gradual metal build‐up. Therefore, routine monitoring of feed quality and sediment conditions is critical for safe aquaculture practices. These findings offer valuable guidance for hatchery operators and fish farmers, emphasising the need for preventive strategies to ensure the sustainable and safe production of tilapia.